Determinant factors influencing the nutrition status of adolescents with intellectual disabilities: a scoping review - Suwito, Maria Rebecca; Widyastuti, Nurmasari; Rahadiyanti, Ayu; Anjani, Gemala; Nurhidayati, Lisa Rosyida (BKM Public Health and Community Medicine, 2025)
Purpose: This scoping review aims to explore the determinants influencing the nutritional status of adolescents with intellectual disabilities, including macronutrient intake, family income, and other contributing factors. Methods: A systematic search was conducted for articles published from 2012 to 2022 in PubMed, ScienceDirect, and Scopus databases, using keywords such as "nutritional status," "dietary intake," "family income," "intellectual disability," and "adolescent". Relevant studies were selected through title and abstract screening, followed by full-text review, resulting in nine articles for analysis. Results: The review found that inadequate dietary intake, particularly high consumption of unhealthy foods, significantly impacts the nutritional status of adolescents with intellectual disabilities. Family income, while affecting food security, does not independently determine dietary outcomes. Comorbid conditions like Down syndrome, autism spectrum disorder (ASD), and cerebral palsy, along with physical limitations and the use of psychotropic medications, further contribute to malnutrition risks. Conclusion: Adolescents with intellectual disabilities are at increased risk of malnutrition due to poor food intake. While family income influences food security, it is not the sole factor. The presence of comorbid conditions, physical limitations, and psychotropic medication use is also a key determinant of their nutritional status.